INISIASI MANAJEMEN PENGETAHUAN OLEH KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN PENGETAHUAN GURU TENTANG KEKERASAN ANAK (Studi Kasus Di Kacamatan Balongbendo) - Rachmayanti, Riris Diana (Jurnal PROMKES, 2015)
Backgroud : Violence cases often occur in children and the culprit is 68% known to children, including 34% by the biological parents, and 90% is in the form of physical violence. To overcome this the schools involvement is needed since school as a source of information for parents. But schools are unable to carry out their function as a source of information about domestic violence on children. Therefore, schools need to have knowledge management capabilitiesPurpose : this study was to iniation of knowledge management by principlals to increase the kindergarten teachers knowledge about domestic violence on children Methods : by using pre-experimental design with one group pre test-post test. The number of kindergarten schools being sampled were as many as seven schools with seven principals and 22 teachersResult : The results retrieved that principal value of knowledge about domestic violence on children was (p = 0.137) and knowledge management was (p 0.0005). While teachers knowledge about domestic violence on children before and after the process of knowledge management by the principal values obtained was (p = 0.000).Conclution : There was increased knowledge management of principals, but not necessarily an increase in abillity knowledge management. Knowledge management was influenced by several factors, including organizational conditions, social conditions and technology organization. Increased teacher knowledge is influenced by predisposition factors including prior knowledge, experience, age, teacher education, the ability to absorb the material, and retention of teachersKeywords: child abuse, knowledge management, kindergarten school